Esquistossomose mansônica autóctone no Distrito Federal, Brasil Autochthonous cases of schistosomiasis mansoni in the Federal District, Brazil - Frederico Simões Barbosa (Revista de Saúde Pública, 1979)
Sete casos autóctones de esquistossomose mansônica são descritos no Distrito Federal (Brasil). Todos os casos são de crianças cujas idades variavam de 3 a 13 anos e que habitavam área suburbana da cidade de Planaltina. Cinco destes casos pertencem a uma mesma família vivendo às margens de um criadouro de Biomphalaria glabrata onde foram encontrados dois caramujos infectados por Schistosoma mansoni em 229 examinados. Seven autochthonous cases of schistosomiasis mansoni are described in this paper. All of them refer to children, 3 to 13 years old, living in Planaltina, Federal District, Brazil. Five out of the seven cases belong to the same family living for 14 years in Planaltina. For the last 4 years this family has lived in a wooden hut 40 meters distant from a breeding place of B. glabrata. Of the 229 snails examined, two were naturallv infected with S. mansoni.